Mucosal Injuries by Tegumentary Leishmaniasis: A Systematic Review - Feitosa, Pedro Walisson Gomes; Oliveira, Italo Constancio de; Moura, Rayane da Silva; Grangeiro, Yasmin de Alencar; Rodrigues, Elisa Hellen Cruz; Caracas, Heloísa Fernandes; Pinheiro, Sally de França Lacerda (Amadeus International Multidisciplinary Journal, 2019)
Abstract: American Tegumentary Leishmaniasis (ATL) it’s the name given to the amount of infection diseases that cause immunological and polymorphic changes on the skin and mucosa. Caused by the contamination of protozoa of the genus Leishmania, the pathogenesis in question can manifest itself in the Tegumentary (mucosa and cutaneous) and in the visceral form, depending on the parasite and the host. The aim of this study was to collect the scientific knowledge produced about the Mucosa Tegumentary Leishmaniasis, presenting the epidemiological, clinical, diagnostic and therapeutic relations available in the researched literature. It was applied the Muños Protocol (2002) in published articles between 1981 and 2018 and indexed in the database of the Health Virtual Library (HVL) that was selected for this review study. The research strategy used was: “Tegumentary Leishmaniasis” and “Mucosa”, including, too, the following limits: articles in Portuguese, English and Spanish, available. The works present interfaces of Mucosa Tegumentary Leishmaniasis, stating epidemiological, clinical, diagnostic and therapeutic data of the pathology. It is evidenced the importance of the realization of studies about this theme to the development of new medical treatments. It is noticed that there is still a limited number of researches in this field, becoming necessary new studies about the theme. Keywords: Mucosal injuries. Leishmaniasis. Infection diseases.